VD_FINDINFO HC / 2012 / 615 vom 1. Oktober 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, RESTITUTION DU DÉLAI, LOGEMENT DE LA FAMILLE | 169 CC, 257d al. 1 CO, 257d al. 2 CO, 257d CO, 266m CO, 266n CO, 148 CPC (CH), 149 CPC (CH), 257 CPC (CH)